I'll Buy What You Post! : The Impact of Social Media Influencer on Consumer Purchase Intention - Barokah, Giaza Ananda; Alfansi, Lizar (Almana : Jurnal Manajemen dan Bisnis, 2025)
Traditional marketing is losing effectiveness. Brands are turning to social media influencers to shape consumer behavior. This study definitively investigates the impact of influencer attributes, trustworthiness, attractiveness, and expertise on consumer purchase intention, focusing specifically on the Erigo fashion brand. We used a quantitative approach, collecting data via online questionnaires from Erigo's influencers. We applied Structural Equation Modeling-Partial Least Squares (SEM-PLS) to analyze the relationships between variables. The results are clear: all three influencer attributes significantly influence brand attitude and purchase intention, with expertise showing the strongest effect. Brand attitude also serves as a mediator between influencer attributes and purchase intention. The findings demonstrate that credible influencers enhance consumer trust and foster positive brand perception and purchase intent. This study provides valuable insights into digital consumer behavior and offers strategic guidance for fashion marketers looking to leverage influencer partnerships to boost brand engagement and sales.